EPID-09. Characterizing the epidemiology of radiation-induced gliomas following cranial radiotherapy for pediatric cancers: a population-based study. (3rd June 2022) - Leary, Jacob; Anderson-Mellies, Amy; Green, Adam
Abstract: BACKGROUND: Cranial radiotherapy (RT) is used to treat pediatric central nervous system (CNS) cancers and leukemias. RT carries a risk of secondary CNS malignancies, including radiation-induced gliomas, the epidemiology of which is poorly understood. METHODS: This retrospective study using SEER registry data (1975-2016) included two cohorts. Cohort 1 included patients diagnosed with Grade III/IV or ungraded glioma as a second malignancy >/=2 years after receiving beam radiation and/or chemotherapy for a first malignancy diagnosed at ages 0-19 years, either a primary CNS tumor treated with RT (1a, n=77) or leukemia with unknown RT treatment (1b, n=20). Cohort 2 included patients with possible missed RIG who received RT for a primary CNS tumor diagnosed at 0-19 and then died of presumed progressive disease more than 5 years after diagnosis, since previous studies have documented many missed RIGs in this group (n=296). Controls (n=10, 687) included all other patients ages 0-19 who received RT for a first CNS tumor or leukemia who did not fit inclusion criteria above. RESULTS: For Cohort 1 (likely/definite RIGs), 0.97% of patients receiving cranial RT went on to develop RIG. 3.39% of patients receiving cranial RT for primary CNS tumors fell in Cohort 2 (possible RIGs). Median latency to RIG diagnosis was 11.1 years; latency was significantly shorter for Cohort 1b (median 10.0, range 5.0-16.1) vs. 1a (12.0, 3.6-34.4, p=0.018). Median OS for Cohort 1 was 9.0 months. Receiving surgery, radiation, or chemotherapy were all associated with a non-statistically significant improvement in OS (p 0.1-0.2). CONCLUSION: Within the limitations of a population-based study, 1-4% of patients undergoing cranial RT for pediatric cancers later develop RIG, which is incurable and can occur anywhere from 3-35 years later. Effective treatment of RIG remains unclear and is thus deserving of increased attention in preclinical and clinical studies.